Recurrent hyperparathyroidism due to parathyroid carcinoma - Ellis, H. A. (1971)
The case is described of a woman who died with a functioning parathyroid carcinoma 19 years after removal of two parathyroid tumours, considered at the time to be benign. Following operation hyperparathyroidism subsided, with a short period of hypocalcaemia, and severe osteitis fibrosa cystica healed. Five years before death progressive renal failure developed with normal and later raised serum calcium levels. At necropsy a parathyroid carcinoma infiltrated the thyroid at the site of the previous operation and there was a solitary hepatic metastasis. A remaining parathyroid gland was nodularly hyperplastic and the bones showed evidence of active osteitis fibrosa. The relationship between parathyroid hyperplasia and neoplasia is discussed. Acceptable cases of parathyroid carcinoma are rare, but carcinoma is an important cause of recurrent hyperparathyroidism even months or years after removal of an `adenoma'.